Pengaruh Model Pembelajaran dan Kecerdasan Sosial Terhadap Hasil Belajar Sejarah - agi Hagiaman (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2017)
The purpose of this research is to know the difference of learning result of history between students studying with cooperative learning model of group investigation type with conventional learning model, the influence of interaction between learning model with social intelligence to historical learning result, difference of historical learning result between students who have social intelligence High learning group model investigation with students who have high social intelligence learning with conventional learning model, differences in historical learning outcomes between students who have low social intelligence who learn with group investigation model with students who have low social intelligence learning by model of learning Conventional. The research method used experimental method with factorial design 2x2 by level. The population of this research is students of SMA Negeri 1 Jatisari class XI (eleven) IPS. The sample of research is two classes taken randomly by technique (cluster random sampling). The research instrument uses questionnaires and test results of learning. The result of the research shows that there is influence and difference of the result of history learning between the students who have high social intelligence and low social intelligence that study with cooperative learning model of group investigation type and conventional learning model.